Isolation and Characterization of Bacterial Strains That Are Resistant To Nickel, Cobalt and Other Heavy Metal - Norashikin, Badaruddin Afandi (Universiti Malaysia Sarawak, UNIMAS, 2010)
A total of 500 bacterial strains were isolated from soil samples collected near the non-ferrous industrial sites (industrial effluent) at Pending, Sarawak. Two hundred and thirty bacterial isolates were found to be resistance against Co, Ni, Cu, Zn, Hg and Fe in different patterns of resistance. Heavy metal-resistance pattern to CoR and NiR showed the highest percentage (36%). The levels of resistance of bacterial isolates were determined by testing against various concentrations of heavy metals. Mercury was the most toxic metal which inhibits the growth of bacterial isolates at 15μg/ml. The toxicity order of the metals were Hg > Co > Cu > Ni > Fe > Zn. Five bacterial isolates were selected for further analysis based on their multiple patterns of resistance (CoR NiR CuR FeR ZnR HgR). The morphological and biochemical characteristics of five bacterial isolates showed that they were putative strains of the genus Ralstonia Eutropha (Alcaligenes), Pseudomonas aeruginosa, Klebsiella oxytoca. DNA analysis of all the five representative isolates which showed multiple tolerances of heavy metals did not reveal the presence of any plasmid.